Increase in records of toxic phytoplankton and associated toxins in water samples in the Patagonian Shelf (Argentina) over 40 years of field surveys - Ramírez, Fernando Javier; Guinder, Valeria Ana; Ferronato, Carola; Krock, Bernd (Harmful Algae)
Historical records (1980–2018) of potentially toxic phytoplankton and phycotoxins on the Argentine Continental Shelf (35°S-56.5°S) and adjacent ocean waters were systematically reviewed from scientific literature to assess their abundance and diversity over spatial and temporal scales. Records increased from 124 in the period 1980–1992 to 638 in 2006–2018, and the scanned area expanded from coastal to offshore waters including the shelf-break front. Alexandrium was the most reported genus (54%) during 1980–1992 and Pseudo-nitzschia (52%) during 1993–2005. By 2006–2018, a higher diversity was documented: Alexandrium (20%), Dinophysis (32%), Pseudo-nitzschia (31%), and the most recently described potentially toxic dinoflagellates of the family Amphidomataceae (8%). Likewise, a wider spectrum of phycotoxins was documented in the last decade, with lipophilic (LSTs) and paralytic shellfish toxins (PSTs) as the most recorded. Increased records are related to intensified monitoring, more detailed taxonomic analyses and more sensitive chemical techniques for marine biotoxin detection. This quantitative assessment brings light to the widespread occurrence of HABs along contrasting areas of the Patagonian Shelf and sets the basis for ecosystem risk evaluation. Moreover, comparison of toxic phytoplankton reported in the SW Atlantic with those in similar temperate seas in the North Atlantic and the Pacific Ocean, disclose ocean basin differences in strain toxicity of A. ostenfeldii, D. tripos and Azadinium species. Fil: Ramírez, Fernando Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina Fil: Guinder, Valeria Ana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina ...